Synthesis of silica-supported nanoiron for Cr(VI) removal: application of Box-Behnken Statistical Design (BBD) - Praewpatra Archariyapanyakul; Bhuckchanya Pangkumhang; Pummarin Khamdahsag; Visanu Taboonchuy (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study aimed to optimize the condition of silica-supported nanoscale zero valent iron (NZVI/SiO2) synthesis by colloidal impregnation method. Box-Behnken design (BBD) was used as a tool to create and analyze the 17 synthesized conditions of NZVI/SiO2 samples. The independent variables included ethanol concentration (0-100 vol%), amount of silica (0.025-0.125 g) and agitation speed (100-400 rpm). In addition, analysis of variance (ANOVA) for a response surface quadratic model was used to approximate statistical relationship of independent variables. The reducing performance of the synthesized NZVI/SiO2 was examined through removal of Cr(VI) contaminated in water. The optimum of NZVI/SiO2 synthesis was validated with 100 vol% of ethanol concentration, 0.075 g of silica amount, and 100 rpm of agitation speed. The materials were characterized using X-ray diffraction (XRD), scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM-EDX), and nitrogen adsorption/desorption which showed the existence of NZVI phase, composition, and morphology. The Cr(VI) removal efficiency of the NZVI/SiO2 was tested further at the solution pH 4, 7 and 10 in comparison with that by pristine NZVI and silica-unsupported NZVI (NZVI + SiO2). Among the three materials, NZVI/SiO2 presented the highest Cr(VI) removal, especially at pH 7 and 10 with 98 and 94.41%, within 60 min. This was due to the adsorption of Cr(OH)3 and Fe(OH)3 precipitates over SiO2 resulting in availibilty of NZVI/SiO2’s active sites. The proposed mechanism of Cr(VI) removal by NZVI/SiO2 was also described.